2008
DOI: 10.4049/jimmunol.181.6.3923
|View full text |Cite
|
Sign up to set email alerts
|

CD137 Induces Proliferation of Murine Hematopoietic Progenitor Cells and Differentiation to Macrophages

Abstract: CD137 is a member of the TNFR family, and reverse signaling through the CD137 ligand, which is expressed as a cell surface transmembrane protein, costimulates or activates APCs. CD137 and CD137 ligand are expressed on small subsets of bone marrow cells. Activation of bone marrow cells through CD137 ligand induces proliferation, colony formation and an increase in cell numbers. Compared with total bone marrow cells, the small subpopulation of progenitor cells that express no lineage markers but express CD117 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 37 publications
4
40
3
Order By: Relevance
“…1B). However, the treatment of cells with soluble CD137-Fc had no effect on cell viability and cellular adherence to the culture dishes (data not shown), as previously reported in immune cells (Jiang et al, 2008).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…1B). However, the treatment of cells with soluble CD137-Fc had no effect on cell viability and cellular adherence to the culture dishes (data not shown), as previously reported in immune cells (Jiang et al, 2008).…”
Section: Resultssupporting
confidence: 63%
“…It has previously been reported that CD137 is expressed in a wide range of cell types including monocytes (Langstein et al, 1998), epithelial cells (Schwarz et al, 1995) and hematopoietic stem cells (Jiang et al, 2008). Recently, several reports have also shown that brain cells constitutively express CD137 and its ligand (Reali et al, 2003;Yeo et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…15 Two recent studies demonstrated that CD137L is expressed on hematopoietic stem/progenitor cells in mice. 38, 39 Lee and coworkers reported that CD137L regulates myelopoiesis and inhibits differentiation of mouse hematopoietic progenitor cells. 38 is tempting to speculate on a potential role of CD137L in blocking differentiation of AML blasts and thus AML pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al, reported that CD137L reverse signals inhibit myelopoiesis and the development of DC [33]. On the other hand, others showed that CD137L ligation enhances proliferation of hematopietic progenitor cells and its differentiation to monocytes, macrophages [34,35]. Reverse signals of CD137L enhances DC maturation and subsequent antigen-specific T-cell differentiation [36].…”
Section: Discussionmentioning
confidence: 99%